PENGARUH TINGKAT PEMAHAMAN, PELATIHAN DAN PENDAMPINGAN APARATUR PEMERINTAH DAERAH TERHADAP PENERAPAN ACCRUAL BASIS DALAM PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN JEMBER (STUDI KASUS PADA DINAS PEMERINTAHAN KABUPATEN JEMBER) - Halen Halen; Diana Dwi Astuti (RELASI : JURNAL EKONOMI, 2013)
The study, entitled "Effect of Understanding, Training and Mentoring Against Local Government Reform Implementation of Accrual Basis in Financial Management in Jember (case study at the county government office Jember)". Objective: to determine the effect of simultaneous partial and independent variables (level of understanding, training and mentoring) local government officials on the dependent variable (accrual basis) in the financial management area in Jember district.Samples of this study were all in the district offices as SKPD Jember in charge records and create financial reports (financial section). To determine the effect of independent variables on the dependent variable distributing questionnaires in the financial section of each department. The questionnaire consisted of closed questions where measurement using likkert scale. With five levels, namely strongly agree, agree, disagree, disagree and strongly disagree or very familiar, familiar, less familiar, very less and do not know at all. Through the deployment of the questionnaire, the respondent's answer is then supplied to a predetermined value and then tabulated. Furthermore the raw data were analyzed using multiple linear regression, the data  quality test which consists of test validity and reliability test, F test and t test. The results of calculations performed turned out that the influence of independent variables (level of understanding, training, mentoring) or partially simultaneously have a significant influence on the dependent variable (the application of accrual basis).